First simultaneous measurement of the top quark mass in the lepton+jets and dilepton channels at CDF - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
We present a measurement of the mass of the top quark using data corresponding to an integrated luminosity of 1.9fb-1 of pp̄ collisions collected at s=1.96TeV with the CDF II detector at Fermilab's Tevatron. This is the first measurement of the top quark mass using top-antitop pair candidate events in the lepton+jets and dilepton decay channels simultaneously. We reconstruct two observables in each channel and use a nonparametric kernel density estimation technique to derive two-dimensional probability density functions from simulated signal and background samples. The observables are the top quark mass and the invariant mass of two jets from the W decay in the lepton+jets channel, and the top quark mass and the scalar sum of transverse energy of the event in the dilepton channel. We perform a simultaneous fit for the top quark mass and the jet energy scale, which is constrained in situ by the hadronic W boson mass. Using 332 lepton+jets candidate events and 144 dilepton candidate events, we measure the top quark mass to be Mtop=171.9±1. 7(stat+JES)±1.1(othersyst)GeV/c2=171.9±2.0GeV/c2. © 2009 The American Physical Society.